Kaum Muda Pelaku Gaya Hidup Zero Waste sebagai Generasi Global - Azkiyatun Nufus Firani (Jurnal Studi Pemuda, 2022)
To fulfil their daily needs, youth who practice a zero waste (ZW) lifestyle can shop at an eco-bulk store (eco-friendly store) –taking an example of Ranah Bhumi which is located in Prawirotaman, Yogyakarta. On a large-scale however, the consumption practices in eco bulk stores and the implementation of ZW lifestyle have become an arena for seizing capital opportunities as well as a way for the youth to differentiate themselves as part of the global generation. Using a multi-sited ethnographic method, this research focuses on examining how youth as ZW practitioners become part of the global generation through habitus, in addition, to identifying factors behind the consumption practices of these youth at Ranah Bhumi using green consumerism and youth culture theory. The research found that the youth’s ZW lifestyle habit was formed by their parents, friends, community and social media. This structure is also shaped by the youth’s high mobility in the global realm which embodies their awareness of global lifestyle and environmental issues. The consumption practices and implementation of ZW lifestyle are also an attempt to establish class positions as well as relations among the youth as capital. They categorize themselves as mindful people who are presumably better than their parents’ generation and even their peers, although in fact, they are also immersed by the existing ‘green’ discourse.